INNV-43. NUCLEIC ACID ADEQUACY FROM ARCHIVED FORMALIN-FIXED PARAFFIN EMBEDDED (FFPE) TUMOR TISSUE FOR NEXT-GENERATION SEQUENCING (NGS) IN NATIONAL CANCER INSTITUTE (NCI)- NATURAL HISTORY STUDY (NHS) OF PRIMARY CNS TUMOR. (5th November 2018) - Briceno, Nicole; Crandon, Sonja; Vera, Elizabeth; Siegel, Christine; Aboud, Orwa; Brown, Miranda; Chung, Hye-Jung; Ji, Ming; Levine, Jason; Patel, Snehal; Reyes, Jennifer; Raffeld, Mark; et al.
Abstract: BACKGROUND: A unified data collection system for interrogating the clinical trajectory of patients and their molecular pathology is of significant diagnostic, research, and therapeutic importance. The NCI-NHS follows primary CNS tumor patients throughout their disease. A targeted NGS panel was developed for clinical screening of mutations in 56 genes, 21 copy number alterations, and 25 gene fusion pairs using archived FFPE tissue. Due to the nature of study, available specimens range in age and source, posing a considerable challenge to obtaining an adequate quality and quantity of nucleic acid for genomic analysis. METHODS: Tumor blocks or unstained slides were received for macrodissection of neuro-pathologist scored tumor tissue. DNA and RNA were extracted, using the Qiagen AllPrep FFPE Kit on a semi-automated QIAcube instrument, and sequenced on Ion Torrent NGS platform. RESULTS: Tissue material from 227 patients was submitted, 17(8%) were rejected for low tumor content (<10%) and/or insufficient tissue. In total, 221 specimens were processed from 210 patients. Specimen ages as follows: < 5 years old, 69%; 5–9 years, 22%; ≥10 years, 9%. DNA was successfully sequenced for 99.5% of these cases. RNA sequencing success rate was 85% overall, with 91% for specimens <5 years old, 73% for 5–9 years, and 53% for ≥ 10 years. There was no significant difference between NIH and outside cases. Clinically significant molecular findings were reported in 81% of the cases across 18 diagnoses. High grade tumors comprised 78% of those calls. CONCLUSION: Robust variant calling for a variety of clinical specimens is critical in genetic medicine. Using our protocol, archived FFPE tumor specimen provided high quality NGS results, regardless of originating institution. Additionally, RNA from tissue over 5 years of age had a 71% sequencing success rate. This study confirms the feasibility of using archived materials for molecular analysis with analyzable results.